2011
DOI: 10.1152/ajpheart.00635.2011
|View full text |Cite
|
Sign up to set email alerts
|

GATA6 reporter gene reveals myocardial phenotypic heterogeneity that is related to variations in gap junction coupling

Abstract: This study examined transgenic mice whose expression of a β-galactosidase (lacZ) reporter is driven by a GATA6 gene enhancer. Previous investigations established that transcription of the transgene was associated with precardiac mesoderm and primary heart tube myocardium, which decreased progressively, so that its expression was no longer observed within ventricular myocardium by midgestation. Expression of this reporter in the adult was investigated for insights into myocyte homeostasis and cardiovascular bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…GATA6 is an upstream transcriptional regulator of multiple genes expressed during embryogenesis and cardiac morphogenesis, including the genes that encode atrial natriuretic factor (ANF), brain natriuretic peptide, α-myosin heavy chain, β myosin heavy chain, and gap junction protein connexin-40 (52). Therefore, the functional characteristics of the GATA6 mutations may be delineated by assessing the transcriptional activity of the ANF promoter in cultured cells.…”
Section: Discussionmentioning
confidence: 99%
“…GATA6 is an upstream transcriptional regulator of multiple genes expressed during embryogenesis and cardiac morphogenesis, including the genes that encode atrial natriuretic factor (ANF), brain natriuretic peptide, α-myosin heavy chain, β myosin heavy chain, and gap junction protein connexin-40 (52). Therefore, the functional characteristics of the GATA6 mutations may be delineated by assessing the transcriptional activity of the ANF promoter in cultured cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that GATA6 is an upstream regulator of some genes expressed during cardiac development, including β myosin heavy chain, atrial natriuretic peptide, and gap junction genes [6,12], and mutations in several target molecules have been linked to AF [5]. Therefore, mutated GATA6 probably confers susceptibility to AF by reducing expression of target genes.…”
mentioning
confidence: 99%
“…Previous studies have revealed that GATA6 is an upstream transcriptional regulator of several genes expressed during cardiac development, including genes that encode atrial natriuretic peptide, brain natriuretic factor, gap junction protein, and β-myosin heavy chain (40). GATA6 may bind to downstream target DNA alone or together with other partners including NKX2-5, GATA4, GATA5 and TBX5, and the synergistic transcriptional activations mediated by these transcription factors have been substantiated (36,41,42).…”
Section: Discussionmentioning
confidence: 97%